Whole genome sequence and genome annotation of Colletotrichum acutatum, causal agent of anthracnose in pepper plants in South Korea - Han, Joon-Hee (Genom Data, 2016)
Colletotrichum acutatum is a destructive fungal pathogen which causes anthracnose in a wide range of crops. Here we report the whole genome sequence and annotation of C. acutatum strain KC05, isolated from an infected pepper in Kangwon, South Korea. Genomic DNA from the KC05 strain was used for the whole genome sequencing using a PacBio sequencer and the MiSeq system. The KC05 genome was determined to be 52,190,760 bp in size with a G + C content of 51.73% in 27 scaffolds and to contain 13,559 genes with an average length of 1516 bp. Gene prediction and annotation were performed by incorporating RNA-Seq data. The genome sequence of the KC05 was deposited at DDBJ/ENA/GenBank under the accession number LUXP00000000.